Tacit knowledge in organizational learning - Busch, Peter, 1967-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
"This book offers academians and practitioners an illustration of the importance of tacit knowledge to an organization, presenting a means to measure and track tacit knowledge in individuals and recommendations on firm attributes and their ideal utilization of the tacit knowledge resource"--Provided by publisher.
1. Introduction -- 2. Knowledge management -- 3. Tacit knowledge defined -- 4. Testing for tacit knowledge -- 5. Organisations -- 6. Knowledge flows -- 7. Social network analysis -- 8. Methodology -- 9. Initial results -- 10. Results with formal concept analysis -- 11. Large company (X) -- 12. Small company (Y) -- 13. Medium company (Z) -- 14. Discussion -- 15. Conclusions and recommendations.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on July 26, 2010).
Keywords: Knowledge management; Tacit knowledge; Social networks; Organizational learning; Electronic books